Improving oral implant osseointegration in a murine model via Wnt signal amplification. (8th December 2013) - Mouraret, Sylvain; Hunter, Daniel J.; Bardet, Claire; Popelut, Antoine; Brunski, John B.; Chaussain, Catherine; Bouchard, Philippe; Helms, Jill A.
Abstract Aim To determine the key biological events occurring during implant failure and then we use this knowledge to develop new biology‐based strategies that improve osseointegration. Materials and Methods Wild‐type and Axin2LacZ/LacZ adult male mice underwent oral implant placement, with and without primary stability. Peri‐implant tissues were evaluated using histology, alkaline phosphatase (ALP) activity, tartrate resistant acid phosphatase (TRAP) activity and TUNEL staining. In addition, mineralization sites, collagenous matrix organization and the expression of bone markers in the peri‐implant tissues were assessed. Results Maxillary implants lacking primary stability show histological evidence of persistent fibrous encapsulation and mobility, which recapitulates the clinical problems of implant failure. Despite histological and molecular evidence of fibrous encapsulation, osteoblasts in the gap interface exhibit robust ALP activity. This mineralization activity is counteracted by osteoclast activity that resorbs any new bony matrix and consequently, the fibrous encapsulation remains. Using a genetic mouse model, we show that implants lacking primary stability undergo osseointegration, provided that Wnt signalling is amplified. Conclusions In a mouse model of oral implant failure caused by a lack of primary stability, we find evidence of active mineralization. This mineralization, however, is outpaced by robust bone resorption, which culminates in persistent fibrous encapsulation of the implant. Fibrous encapsulation can be prevented and osseointegration assured if Wnt signalling is elevated at the time of implant placement.